Protocol for FRAP-based estimation of nuclear import and export rates in single yeast cells - Durrieu, Lucía (2024)
Here, we present a protocol for estimating nuclear transport parameters in singlecells. We describe steps for performing four consecutive fluorescence recoveryafter photobleaching experiments, fitting the obtained data to an ordinary dif-ferential equations model, and statistical analysis of the fittings using a special-ized R package. This protocol permits the estimation of import and export rates,nuclear or cytosolic fixed fractions, and total number of molecules.For complete details on the use and execution of this protocol, please refer to Durrieu et al.